IMiPACT OF METHYL PARATHION ON LACTATE DEHYDROGENASE ISOZYMES OF A TELEOST TILAPIA MOSSAMBICA (PETERS) - Rao, K Sivaprasada; Ahmad, I Kabeer; Rao, K V Ramana (Indian Journal of Fisheries, 2011)
The electrophoretic patterns of lactate dehydrogenase showed varied distribution of the isozymes in four selected tissues of T. mossambica (Peters). The studies suggest that there are two sub-units which, on random comibination, give rise to five isozymes. The qualitative nature and mobility of the isozymatic patterns of each tissue remained unaltered except for a slight reduction in the intensity of bands under subacute methyl parathion toxicity. However, a decrease in quantitative levels Of LDH, measured by colorimetry, corroborates a fall in intensity of all isozymes. The significance of the results are discussed in relation to physiological stress leading to a manifestation of phenomenon simulating anaerobiosis.